Kemampuan Pemahaman Konsep pada Materi Sistem Persamaan Linear Dua Variabel Ditinjau dari Perbedaan Gender Siswa SMP Kelas VIII - Windi Pebrianti; Nitta Puspitasari (Institut Pendidikan Indonesia, 2023)
Abstract Understanding concepts has an important role in learning mathematics that will strengthen the memory of students in receiving imaginary mathematical material so it is necessary to understand the concepts first. The aim of this study is to find out how the ability of understanding the concepts of male and female students on the material of the System of Linear Equations of Two Variables of High School students of Grade VIII. The type of research used is qualitative research. Study subject of six students of SMP 3 Karangpawitan class VIII. Techniques of data collection of observations, tests, interviews, and documentation. The results of this study male and female students can meet indicators reaffirm a concept already included in a high category; indicators classify objects according to the concept of male students included in the middle category, but female pupils included in high categories; indicator present concepts in the form of mathematical representations of male pupils including the middle class, but feminine pupils already including in the high category, indicators using, exploiting and selecting specific procedures or operations of males and females including the low category; indicators apply concepts or algorithms of male and feminine students including the medium category. Abstrak Pemahaman konsep mempunyai peranan penting dalam pembelajaran matematika yang akan menguatkan ingatan siswa dalam menerima materi matematika yang bersifat imajiner sehingga diperlukan memahami konsepnya terlebih dahulu. Tujuan penelitian ini untuk mengetahui bagaimana kemampuan pemahaman konsep siswa laki-laki dan perempuan pada materi Sistem Persamaan Linear Dua Variabel Siswa SMP Kelas VIII. Jenis penelitian yang digunakan adalah penelitian kualitatif. Subjek penelitian enam siswa SMP 3 Karangpawitan kelas VIII. Teknik pengumpulan data observasi, tes, wawancara, dan dokumentasi. Hasil penelitian ini siswa laki-laki dan perempuan dapat memenuhi indikator menyatakan ulang sebuah konsep sudah termasuk kategori tinggi; indikator mengklasifikasikan objek sesuai konsepnya siswa laki-laki termasuk kategori sedang, siswa perempuan termasuk kategori tinggi; indikator menyajikan konsep dalam bentuk representasi matematis siswa laki-laki termasuk kategori sedang, siswa perempuan sudah termasuk kategori tinggi; indikator menggunakan, memanfaatkan dan memilih prosedur atau operasi siswa laki-laki dan perempuan termasuk kategori rendah; indikator mengaplikasikan konsep atau algoritma siswa laki-laki dan perempuan termasuk kategori sedang.